Management of intercondylar fractures of the distal humerus in adults using bi-columnar plating through trans-olecranon approach - Yadav, Vijendra; Ganie, Parvez Ahmad; Prasad, Rajendra Pranav; Jeyaraman, Madhan (International Journal of Research in Orthopaedics, 2021)
Background: Inter-condylar fractures of the distal humerus are uncommon injuries and present the most difficult challenge among fractures of the lower end of the humerus. The principle involves anatomical reduction and fixation with stabilization of extra-osseous implants. The functional outcome has been greatly influenced by the early graduated rehabilitative exercise. We aimed to evaluate the functional outcome of inter-condylar fractures of the distal humerus in adults using bi-columnar plating through a trans-olecranon approach. Methods: A prospective study with 40 adult patients with inter-condylar fracture of the distal humerus were managed with bi-columnar plating through a trans-olecranon approach and were followed up for 12 months. The functional outcome was analysed by Mayo’s Elbow Performance Score (MEPS) at the end of 12 months follow up. Results: The average age of study participants were 50.8 years. A total of 24 cases were due to RTA and 16 cases were due to direct falls. Out of 40 cases, 6 (15%) were of B1 type, 2 (5%) were of type B2, 12 (30%) were of C1, 10 (25%) of C2, and 10 (25%) were of the type of C3 according to AO classification. According to MEPS at the end of the 12th-month follow-up, excellent results were seen in 24 (60%), good in 8 (20%), fair in 6 (15%), and poor results in 2 (5%) cases. Conclusions: Anatomically, bi-columnar plating for distal humerus is useful in providing stable fixation for complex distal articular fractured by trans-olecranon approach and facilitating early postoperative rehabilitation. Clinical and radiological results showed a good healing rate with a good range of motion.